Effect of different levels of dietary cottonseed oil on broiler chicks production - Mohammed, Mohammed Omar Abdalqadir; Mirghani, Mohamed Elwathig Saeed; Arabi, Sami Ahmed Mohammed (IIUM PRESS, 2018)
This study was conducted to evaluate the effect of dietary cottonseed oil (CSO) at different levels on broiler chickens. Dietary CSO was tested for energy supplementation values in poultry at levels 0, 3, 6 and 9% utilizing isonitrogenous (22.5% CP), semi-isocaloric (3100Kcal/kg) rations and run in the experiment. Ninety-six seven-day old unsexed Ross-308 broiler chicks with an initial weight of 72.9g were used for each experiment in a completely randomized design (4x4x6). Chicks were fed for 42 days. Supplementation with the oils improved performance (p>0.05) but CSO gave significant (p<0.05) values in final, weight gain and feed conversion ratio. Results of energy retention showed similar values in initial energy, but final and gained energy revealed significant (p<0.05) differences among treatment groups. Feed intake, weight gain and final weights of birds were significantly reduced (p<0.05) across treatments by the increased dietary inclusion of CSO while feed conversion ratio of birds increased significantly with increasing dietary CSO (P<0.05). Also, hematological values, serum metabolites, enzyme activities and electrolytes, the packed cell volume (PCV), hemoglobin (Hb) and white blood cell (WBC) varied significantly (P<0.05) with inclusion. Adding 3-6% of the oil improves the carcass, the feed intake, feed conversion efficiency, and the profitability margin.